Pengendalian Pedagang Kaki Lima (PKL) Oleh Satuan Polisi Pamong Praja (SATPOL PP) Kabupaten Sidoarjo di Taman Pinang Indah - Berliana Aji Anggraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The problem of illegal street vendors in Sidoarjo Regency continues to occur, especially in the Taman Pinang Indah Housing area, Sidoarjo Regency. This requires the Sidoarjo Regency Government to maximize efforts to regulate and control street vendors in the Taman Pinang area through the Sidoarjo Regency Public Order Agency (Satpol PP). This study aims to further examine how the efforts to control street vendors by the Sidoarjo Regency Satpol PP in the Taman Pinang Indah area are in accordance with Sidoarjo Regent Regulation Number 47 of 2018 concerning Control of Street Vendor Order and Parking. The method used in this study is descriptive qualitative by conducting interviews and observations as well as documentation as a method of data collection. After going through data analysis with data analysis techniques by Miles & Huberman, the results of the study indicate that the efforts to inventory street vendors by Satpol PP and the Sidoarjo Regency Government have been carried out well and have been made to the maximum, especially in determining new locations to relocate street vendors so as not to disrupt access roads in and out of the Taman Pinang Indah Housing despite encountering a number of obstacles. Furthermore, in the restriction efforts, the Sidoarjo Regency Public Order Agency (Satpol PP) encountered obstacles that caused this process to run slowly and difficult, one of which was the rioting actions by street vendors. Finally, the process of controlling street vendors was carried out through Condition Creation Patrols, accompanied by the issuance of warnings and sanctions to street vendors who violated. The Sidoarjo Regency Government has basically made every effort to resolve and avoid ongoing conflict between street vendors and Taman Pinang Indah residents through relocation, but it turns out that until now this remains homework that must be completed by the Sidoarjo Regency Government.